The acoustics of the early-Christian monuments of thessaloniki - TZEKAKIS, Emmanuel G. (Archives of Acoustics, 1981)
This paper is the last of a series of four papers concerning the acoustics of historic monuments and churches of Thessaloniki. All monuments dealt with in these series have been built inside the very center of the old walled part of the town.Although Thessaloniki has suffered many destructions, a number of fourteen buildings with some interest for the room acoustics, are to be found today witnessing her over two thousand year old history. Of these buildings five come from the early-Christian era, 4th to 7th century, and nine from the Byzantine era, 11th to 14th century.The present -paper reports on data accumulated on the first group of five early-Christian monuments, while data on the other group is at the moment already in print [4].After the descriptions of the monuments and the measurement results, a discussion follows, comparing the main characteristics of both groups.